(untitled) (Global Journal of Human-Social Science, 2023)
In the world within the framework of population needs environment commitments economy trends societal facts and infrastructures urbanization planning and smart urban experience are common concerns to provide sustainable living areas in developed and developing countries Similarly the digital revolution has transformed citizens daily life through the adoption of socio-digital technologies resulting in a transition of traditional cities to smart city models